Prognostic Role Of The European Society Of Cardiology Model And Simplified Pulmonary Embolism Severity Index In Pulmonary Embolism: Results From The Turkey Pulmonary Embolism Group (tupeg) Study - Ozlu, T.; Ozsu, S.; Senturk, A.; Ucar, E. Yilmazel; Kirkil, G.; Kadioglu, E. Ekbic; Uysal, A. (Amer Thoracic Soc, 2014)
[Abstract Not Available]